Routledge companion to digital consumption - Belk, Russell W; Llamas, Rosa (London Routledge, 2013)
"The first generation that has grown up in a digital world is now in our university classrooms. They, their teachers, and their parents have been fundamentally affected by the digitization of text, images, sound, objects and signals. They interact socially, play games, shop, read, write, work, listen to music, collaborate, produce and co-produce, search and browse very differently than in the pre-digital age. Adopting emerging technologies easily, spending a large proportion of time online, and multitasking are signs of the increasingly digital nature of our everyday lives. Yet consumer research is just beginning to emerge on how this affects basic human and consumer behaviours such as attention, learning, communications, relationships, entertainment and knowledge. The Routledge Companion to Digital Consumption offers an introduction to the perspectives needed to rethink consumer behaviour in a digital age that we are coming to take for granted and which therefore often escapes careful research and reflective critical appraisal"--
"The first generation that has grown up in a digital world is now in our university classrooms. They, their teachers and their parents have been fundamentally affected by the digitization of text, images, sound, objects and signals. They interact socially, play games, shop, read, write, work, listen to music, collaborate, produce and co-produce, search and browse very differently than in the pre-digital age. Adopting emerging technologies easily, spending a large proportion of time online and multitasking are signs of the increasingly digital nature of our everyday lives. Yet consumer research is just beginning to emerge on how this affects basic human and consumer behaviours such as attention, learning, communications, relationships, entertainment and knowledge. The Routledge Companion to the Digital Consumer offers an introduction to the perspectives needed to rethink consumer behaviour in a digital age that we are coming to take for granted and which therefore often escapes careful research and reflective critical appraisal"--
Includes bibliographical references and index.
Keywords: Information technology -- Social aspects; Consumer behavior; Consumers -- Research; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Marketing / Direct